The changed – and changing – landscape of serials publishing: Review of the literature on emerging models. Issue 3 (17th February 2020) - Herman, Eti; Akeroyd, John; Bequet, Gaelle; Nicholas, David; Watkinson, Anthony
Abstract : This article presents an up‐to‐date portrayal of the greatly changed landscape of scholarly journal publishing and identifies the emerging trends characterizing it. We consider the attributes, novelty, and disruptive potential of different models, which range from improvements to the extant model to attempts at reconfiguration and transformation. We propose that journal transition can be seen as falling into three categories. The first is enhanced models of the traditional scholarly journal, which typically afford enriched functionality that breaks the bonds of the printed page whilst otherwise remaining wholly traditional in their offerings. The second category is innovative models of the traditional scholarly journal, which aim at supporting the journal in performing its traditional roles through convention‐altering ways. The third category is the possible alternatives to the traditional journal, which represent a move towards alternative modes of knowledge dissemination. This review shows that each of the models identified makes contributions to enriching the reporting and showcasing of scholarly output. They also make it more effective and more efficient. However, we conclude that none of the possible alternatives being discussed can serve as a full‐fledged alternative to the journal.